Ritual and event interdisciplinary perspectives - Franko, Mark (Routledge advances in theatre and performance studies, 2007)
"Catastrophic contemporary events challenge ritual's power to reconcile and heal the destitute, disenfranchised, and dying. The essays in this book reasses and revise the traditionally understood relationships between ritual and politics, ritual and everyday life, ritual and art making, and ritual and disaster in the post-Hiroshima, HIV/AIDS, 9/11 era. The contributions range in subject matter from choreography, film, photography, and visual culture to theatre, religious studies, semiotics and literature. The essays are unified by the question: how can ritual confront the event today?"--Book jacket.